Boy's night out - Hargrove, Marion 1919-2003; Wallach, Ira 1913-1995 (Turner Entertainment Co., 2010)
Bowling? Nope. Another round of beers? Yawn. Three married men and their divorced buddy want to try something more intriguing on their boys' night out: a boy's night in with a blonde tootsie in a secret love pad. Unknown to them, the tootsie is really a doctoral student researching the love life of the suburban male. And she proves her smarts by keeping all four relationships strictly platonic, despite the boys' boasting to the contrary
Title from container
Orig., USA, 1962
Keywords: Filmkomödie; Married men / Drama; Middle class men / Drama; Married men; Middle class men; Comdey films; Comedy films; Drama; Feature films; Fiction films; Films comiques; Films de fiction; Film; DVD-Video